The factors affecting the adjustment of a group of turkish dual diploma students in the usa: english proficiency and cultural differences - Yildirim, Ozgur ((JELE) Journal Of English Language and Education, 2018)
The purpose of this qualitative study was to investigate the adjustment problems experienced by a group of Turkish dual diploma students studying in the USA. The participants of the study were 18 undergraduate Turkish students studying in the Environmental Engineering and Civil Engineering dual diploma programs offered by a state university in New York and a state university in Turkey. The data were collected by using 15 interview questions and were analyzed by using constant comparative method in which emerging categories were identified in the interview transcripts and themes were developed from those categories. Analysis of the data indicated six major categories of the factors affecting the adjustment problems: differences in educational systems of the two institutions; English proficiency; the unique design of the program; cultural differences between the two countries; tendency to form and stay in cliques of dual diploma students; and orientation.